Bardoxolone Methyl Ameliorates Myocardial Ischemia/Reperfusion Injury by Activating the Nrf2/HO-1 Signaling Pathway - Anwu Huang; Zhaolin Wang; Hua Tang; Zhuyin Jia; Xiaojun Ji; Xuehua Yang; Wenbing Jiang (Hindawi-Wiley, 2023)
Background. Myocardial ischemia/reperfusion (I/R) injury is a severe heart problem resulting from restoring coronary blood flow to the myocardium after ischemia. This study is aimed at ascertaining the therapeutic efficiency and action mechanism of bardoxolone methyl (BARD) in myocardial I/R injury. Methods. In male rats, myocardial ischemia was performed for 0.5 h, and then, reperfusion lasted for 24 h. BARD was administrated in the treatment group. The animal's cardiac function was measured. Myocardial I/R injury serum markers were detected via ELISA. The 2,3,5-triphenyltetrazolium chloride (TTC) staining was used to estimate the infarction. H&E staining was used to evaluate the cardiomyocyte damage, and Masson trichrome staining was used to observe the proliferation of collagen fiber. The apoptotic level was assessed via the caspase-3 immunochemistry and TUNEL staining. Oxidative stress was measured through malondialdehyde, 8-hydroxy-2'-deoxyguanosine, superoxide dismutase, and inducible nitric oxide synthases. The alteration of the Nrf2/HO-1 pathway was confirmed via western blot, immunochemistry, and PCR analysis. Results. The protective effect of BARD on myocardial I/R injury was observed. In detail, BARD decreased cardiac injuries, reduced cardiomyocyte apoptosis, and inhibited oxidative stress. For mechanisms, BARD treatment significantly activates the Nrf2/HO-1 pathway. Conclusion. BARD ameliorates myocardial I/R injury by inhibiting oxidative stress and cardiomyocyte apoptosis via activating the Nrf2/HO-1 pathway.